Comparison of computerized and manual versions of the wisconsin card sorting test on schizophrenia and healthy samples - Çelik, Samet; Oğuz, Mustafa; Konur, Umut; Köktürk, Fürüzan; Atasoy, Nuray (American Psychological Association, 2021)
This study aims to examine whether there is an equivalence between the two different versions of Wisconsin Card Sorting Test (WCST) regarding psychometric properties on two distinct samples: individuals diagnosed with schizophrenia and those who are healthy. A total of 504 individuals were included in the study, 243 were diagnosed with schizophrenia, and 261 were healthy individuals. Both samples were separated into two subsamples, and the individuals in each separated group were administered either WCST-C (computerized) or WCST-M (manual) version of the test. We compared statistical measures of mean and variance with the data obtained from the two samples. We carried out analyses related to parallel forms reliability and equality of variances of the tests scores produced by parallel forms of the WCST. There was no significant difference between mean values of manual and computerized versions administered for each sample. However, the patterns of variances of the obtained scores were dissimilar. According to these findings, the two versions were found to be inequivalent regarding psychometric properties.

This study aims to examine whether there is an equivalence between the two different versions of Wisconsin Card Sorting Test (WCST) regarding psychometric properties on two distinct samples: individuals diagnosed with schizophrenia and those who are healthy. A total of 504 individuals were included in the study, 243 were diagnosed with schizophrenia, and 261 were healthy individuals. Both samples were separated into two subsamples, and the individuals in each separated group were administered either WCST-C (computerized) or WCST-M (manual) version of the test. We compared statistical measures of mean and variance with the data obtained from the two samples. We carried out analyses related to parallel forms reliability and equality of variances of the tests scores produced by parallel forms of the WCST. There was no significant difference between mean values of manual and computerized versions administered for each sample. However, the patterns of variances of the obtained scores were dissimilar. According to these findings, the two versions were found to be inequivalent regarding psychometric properties.
Keywords: Wisconsin Card Sorting Test; Wisconsin Card Sorting Test; Computerized Version; Computerized Version; Schizophrenia; Schizophrenia; Equivalence; Equivalence